On the problem of differential diagnosis in the detection of antineutrophil cytoplasmic antibodies - O. N. Egorova; G. M. Tarasova; B. G. Issaeva; A. V. Datsina; D. S. Dilmanova; S. M. Issaeva; M. G. Nogaeva; A. G. Issaeva; A. S. Amanzholova; M. M. Saparbayeva; A. A. Atasheva; A. B. Kanapina (Современная ревматология, 2024)
Vasculitides associated with antineutrophil cytoplasmic antibodies (ANCA) are a group of systemic autoimmune diseases characterized by necrotizing lesions of the walls of predominantly small vessels and the presence of ANCA against proteinase 3 or myeloperoxidase. However, an increase in ANCA levels can also be observed in other diseases, including autoimmune, malignant and infectious diseases, which complicates the interpretation of clinical and laboratory data and requires a differential diagnosis.